Vaginal Leiomyoma: Case Report - Arif, Muliati; Irianta, Trika; B. Farid, Retno (International Journal of Psychosocial Rehabilitation, 2020)
Leiomyomas are the most common pelvic tumor in women, and they arise in reproductive-age women. They are usually described according to their location in the uterus. Vaginal leiomyoma is a rare case. Mrs. R, 24 years old, primipara, presented with vaginal mass. Vaginal examination revealed a mass in the lateral right vaginal wall measuring 6 x 5 x 4 cm. A pelvic CT scan was performed, revealing a homogenous mass with low density and smooth borders inside the vaginal cavum. Vaginal myomectomy was performed. Histopathology revealed a benign leukemia. There was no complications during hospital care, and she was sent home on her 3rd day after the surgery. Vaginal leiomyoma is the most common mesenchymal neoplasm of the vagina. Vaginal leiomyoma should be considered in women with mass in the vagina.